Continuing Reassortant of H5N6 Subtype Highly Pathogenic Avian Influenza Virus in Guangdong - Yuan, Runyu; Wang, Zheng; Kang, Yinfeng; Wu, Jie; Zou, Lirong; Liang, Lijun; Song, Yingchao; Zhang, Xin; Ni, Hanzhong; Lin, Jinyan; Ke, Changwen (Frontiers in Microbiology, 2016)
First identified in May 2014 in China’s Sichuan Province, initial cases of H5N6 avian influenza virus (AIV) infection in humans raised great concerns about the virus’s prevalence, origin, and development. To evaluate both AIV contamination in live poultry markets (LPMs) and the risk of AIV infection in humans, we have conducted surveillance of LPMs in Guangdong Province since 2013 as part of environmental sampling programs. With environmental samples associated with these LPMs, we performed genetic and phylogenetic analyses of 10 H5N6 AIVs isolated from different cities of Guangdong Province from different years. Results revealed that the H5N6 viruses were reassortants with hemagglutinin (HA) genes derived from clade 2.3.4.4 of H5-subtype AIV, yet neuraminidase (NA) genes derived from H6N6 AIV. Unlike the other seven H5N6 viruses isolated in first 7 months of 2014, all of which shared remarkable sequence similarity with the H5N1 AIV in all internal genes, the PB2 genes of GZ693, GZ670, and ZS558 more closely related to H6N6 AIV and the PB1 gene of GZ693 to the H3-subtype AIV. Phylogenetic analyses revealed that the environmental H5N6 AIV related closely to human H5N6 AIVs isolated in Guangdong. These results thus suggest that continued reassortment has enabled the emergence of a novel H5N6 virus in Guangdong, as well as highlight the potential risk of highly pathogenic H5N6 AIVs in the province.